Metal hypersensitivity in hip, knee and spine surgery - Płusa, Tadeusz; Baranowska, Alicja; Baranowski, Paweł; Dudek, Jan; Baranowska-Kijewska, Joanna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2023)
The number of implanted joint prostheses and damaged spinal components is steadily increasing. At the same time, rejection of the implanted material is observed in operated patients, which manifests itself in both skin and general reactions, as well as loosening and earlier wear of implanted prostheses, which was previously referred to as aseptic reactions. However, it has been shown that in a significant proportion of patients, rejection of implanted material may be caused by hypersensitivity to a specific metal. For this reason, patients qualified for implantation of foreign material, mainly nickel, titanium, chromium, molybdenum, and other alloys, should be subjected to allergy tests to detect possible risks in the form of metal sensitivity reactions.